Novel lipid mediator 7S,14R-docosahexaenoic acid: biogenesis and harnessing mesenchymal stem cells to ameliorate diabetic mellitus and retinal pericyte loss - Lu, Yan; Tian, Haibin; Peng, Hongying; Wang, Quansheng; Bunnell, Bruce A.; Bazan, Nicolas G.; Hong, Song (Frontiers in Cell and Developmental Biology, 2024)
Stem cells can be used to treat diabetic mellitus and complications. ω3-docosahexaenoic acid (DHA) derived lipid mediators are inflammation-resolving and protective. This study found novel DHAderived 7S,14R-dihydroxy-4Z,8E,10Z,12E,16Z,19Z-docosahexaenoic acid (7S,14R-diHDHA), a maresin-1 stereoisomer biosynthesized by leukocytes and related enzymes. Moreover, 7S,14R-diHDHA can enhance mesenchymal stem cell (MSC) functions in the amelioration of diabetic mellitus and retinal pericyte loss in diabetic db/db mice. MSCs treated with 7S,14R-diHDHA were